Procedimentos paramétricos aplicados ao design de moda - Oliveira, Marcelo Cordeiro de (2013)
This research brought two different worlds that the time and technology torn apart. The tailor made clothing made of animals skins became more technical through the years and the artisan took the role of the professional called tailor. This person is responsible for transforming plain textiles into complex tridimensional shapes adapted to the human body. State-of-art technologies are studied in order to solve problems digitally, problems that were handled analogically in the past. In this new world, the drafting, modeling and cutting and sometimes the customer itself are digitalized and processed. This technologies set new ways to work, opening up new possibilities and revealing a broad range of new construction options even before the final assembly. A very wide field of research is open.